Bahagia dalam Perspektif al-Ghazali - Jarman Arroisi (Universitas Darussalam Gontor, 2019)
The standard of person's happiness is vary. The West considers material capacity is ‎considered as a sign that someone is happy. But precisely, such a standard will be ‎different if looked at from Islamic worldview. Happiness is not measured by materials by ‎by its closeness to the Creator of happiness itself. This paper examines the strategy for ‎gaining happiness and its model based on perspective of al-Ghazali. Through an ‎analytical descriptive method, this study found important conclusions they are, first, there ‎are groups of people commit immoral acts such as corruption, collusion and so on; ‎believing in that their activities are able to lead to happiness. Whereas the true happiness ‎according to al-Ghazali is not as such, but happiness is a condition when someone is ‎adept to reach the level of Ma'rifatullah. Second, a method to achieve the ma'rifah al-nafs ‎is one way. It is able to be be achieved by contemplating the goal of man’s creation ‎altogether with their duties and obligations and other questions related to the nature of ‎human existence.‎